Respuesta :
Answer:
10x−3y +55
1.)4-2y+51+7x-y+3x
=55-2y+7x-y+3x
2.)55-2y+7x-y+3x
=55-3y+7x+3x
3.)55-3y+7x+3x
=55-3y+10x
4.)55-3y+10x
=10x-3y+55
Answer:
55 - 3y + 10x OR 11 = x, 55 = y
Step-by-step explanation:
just simplifying
4 - 2y + 51 + 7x - 1y + 3x
4 + 51 - 2y - 1y + 7x + 3x
55 - 3y + 10x
setting equal to zero
4 - 2y + 51 + 7x - 1y + 3x = 0
4 + 51 - 2y - 1y + 7x + 3x = 0
55 - 3y + 10x = 0
55 + 10x = 3y
(55 + 10x) = y
55 - 3y + 10x = 0
55 - 3(55 + 10x) + 10x = 0
55 - 165 - 30x + 20x = 0
110 - 10x = 0
110 = 10x
11 = x
55 - 3y + 10x = 0
55 - 3y + 10(11) = 0
55 - 3y + 110 = 0
165 - 3y = 0
165 = 3y
165/3 = y
55 = y
checking answer:
4 - 2y + 51 + 7x - 1y + 3x = 0
4 + 51 - 2y - 1y + 7x + 3x = 0
55 - 3y + 10x = 0
55 - 3(55) + 10(11) = 0
55 - 165 + 110 = 0
165 - 165 = 0
0 = 0